Evolution of Digital Marketing: How the developments in digital marketing helps provide information by re-shaping the process of the speed and convenience of acquiring the information: A Conceptual Framework (The International Journal for Scientific Research, 2023)
The unprecedented growing of the Internet-the digital revolution-has led to changes in the marketing environment forcing marketers to rethink almost everything they do. The internet is actually a hybrid of media; it is a communications medium, allowing companies to create awareness, provide information, and influence attitudes, as well as pursue other communications objectives. The goal of this study is to build a conceptual framework for understanding the role of digital marketing as a communication tool to provide information, where an interactive media allow for a back-and-forth flow of information whereby users can participate in and modify the form and content of the information they receive in real time. More specifically, the framework focuses on two general dimensions suggested by previous research as significant drivers of online information: time, content. it relies on literature that seeks to understand how the developments in digital marketing helps provide information by re-shaping the process of the speed of acquiring the information and the convenience of acquiring the information. Through a multidisciplinary framework, it proposes a more nuanced picture of the relationship between digital marketing and achieve high-level information communication, along with its implications for future studies in this area.
Keywords: Digital marketing; Create awareness; Provide information; Digital content; Speed; Convenience; Acquiring the information